Orodispersible films - recent developments and new applications in drug delivery and therapy - Morath, Benedict; Sauer, Stefanie; Zaradzki, Marcin; Wagner, Andreas H. (Biochemical pharmacology, 2022)
Orodispersible films (ODF) are innovative drug formulations that introduce a promising approach to pharmacotherapy. They represent single- or multi-layer polymer films that show sufficient stability but disintegrate easily. Often no water is needed for ingestion. Therefore, ODF are suitable for patients with swallowing difficulties such as elderly people, children, or patients with restricted transport in the gastrointestinal tract. Also, to avoid the first-pass effect when the drug is already absorbed via the mucosa. Initially developed as niche products ODFs are currently the subject of industrial and university research as dosage forms for improved application and compliance for medical treatment of a multitude of different diseases. An interesting aspect is that ODF can also be produced in an individualized way. This can support the trend toward personalized medicine. Here, we provide at first an overview of the historical background, characterization, and composition of ODFs. Subsequently, technical aspects of the manufacturing process, including three-dimensional printing technology and inkjet printing will be reviewed. As ODFs are promising drug delivery systems for customized small-scale pharmacy preparations, we place particular emphasis on product examples giving the possibility for individualization for their consumers. Finally, we summarize formulations, applications in development, limitations, and the current patent situation.